2008
DOI: 10.1021/je800273c
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Fish Oil by Fractionation through Supercritical Carbon Dioxide

Abstract: In the present research, the solubility of fish oil in supercritical carbon dioxide was studied at temperatures of (40, 50, 60, and 70) °C and pressures of (13.6, 20.4, and 27.2) MPa. The fractionated fish oil samples collected were then esterified using methanol (with sodium methoxide catalyst). The samples were analyzed by GC to determine the amount of four fatty acid methyl ester (FAME) components extracted, namely, methyl palmitate, methyl oleate, methyl EPA (5,8,11,14, and methyl DHA (4,7,10,13,16,19docos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…The fractionated samples were converted to methyl esters by chemical esterifi cation with methanol. The maximum solubility was achieved at 40°C and 272 bar (Davarnejad et al 2008 ) .…”
Section: Applications To Marine By-productsmentioning
confidence: 94%
See 1 more Smart Citation
“…The fractionated samples were converted to methyl esters by chemical esterifi cation with methanol. The maximum solubility was achieved at 40°C and 272 bar (Davarnejad et al 2008 ) .…”
Section: Applications To Marine By-productsmentioning
confidence: 94%
“…Higher pressure (150 bar) and fl ow rates (5 kg/h) resulted in a higher EPA and DHA concentration and decreased the EPA/DHA ratio (Perretti et al 2007 ) . Moreover, Davarnejad et al ( 2008 ) studied the solubility of menhaden fi sh oil in SC-CO 2 at temperatures from 40°C to 70°C and pressures of between 136 and 272 bar. The fractionated samples were converted to methyl esters by chemical esterifi cation with methanol.…”
Section: Applications To Marine By-productsmentioning
confidence: 99%
“…The operational conditions were chosen considering that fish oil is thermally degradable [17] and that Rubio-Rodríguez et al [14] showed that higher yields of oil from fish by-products were achieved at 250 bar and 40°C. So, in this case, the CLO supercritical extraction was carried out at 250 bar, and the effect of different temperatures on the extraction yield was studied at 50, 60, and 70°C.…”
Section: Supercritical Co 2 Extraction Of Cobia Liver Oilmentioning
confidence: 99%
“…Unsaturated fatty acids from fish oil, mostly processed as esters, is a subject investigated heavily in recent years (Davarnejad et al, 2008). Fig.…”
Section: Expansion Of Mobile Phase and Sample Collecting Systemmentioning
confidence: 99%